Proceedings of the 2017 3rd International Forum on Energy, Environment Science and Materials (IFEESM 2017) 2018
DOI: 10.2991/ifeesm-17.2018.145
|View full text |Cite
|
Sign up to set email alerts
|

Damping Properties of Natural rubber/ Epoxidized Natural Rubber composites with different fillers

Abstract: Natural rubber(NR)/Epoxidized Natural Rubber(ENR)/Carbon black(CB), NR/ENR/silica(SiO2), NR/ENR/ montmorillonoid(MMT) and NR/ENR/carbon nanotube(CNT) were prepared in an open two-roll laboratory mixing mill at 50~60 °C. Curing property and static mechanical property of NR/ENR composites with different fillers were investigated. Damping property of NR/ENR composites with different fillers was operated by dynamic mechanical analysis. Results showed that filler MMT and CNT when adding 10 parts per hundreds of rub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Yueqiong Wang et al have investigated the effect of filler shape on damping property and concluded that filler with lamelar and tubulous shape could enhance the damping property of composites, but mechanical property of composites could decrease due to the aggregation in rubber matrix. 7 In another study, Manuel Alberto Guzmán Sánchez et al have used moving die rheometer (MDR) test, stress relaxation, and creep tests and also compression and shear tests to investigate the viscoelastic behavior of NR-based damping materials. 8 They also concluded that carbon black amount and increased stiffness helps to improve damping properties.…”
Section: Introductionmentioning
confidence: 99%
“…Yueqiong Wang et al have investigated the effect of filler shape on damping property and concluded that filler with lamelar and tubulous shape could enhance the damping property of composites, but mechanical property of composites could decrease due to the aggregation in rubber matrix. 7 In another study, Manuel Alberto Guzmán Sánchez et al have used moving die rheometer (MDR) test, stress relaxation, and creep tests and also compression and shear tests to investigate the viscoelastic behavior of NR-based damping materials. 8 They also concluded that carbon black amount and increased stiffness helps to improve damping properties.…”
Section: Introductionmentioning
confidence: 99%